History of Science in Russia in the 20th century: St. Petersburg as a Case Study - Kolchinsky, Eduard I. (Almagest, 2011)
Abstract The advancement of the history of science in Russia is analyzed in the context of profound social, political and economic dislocations of the 20th century, when the academic community, facing tight ideological control, strove to achieve two goals, which sometimes sharply contradicted each other: to respond to requests of the party-state authorities, and to maintain their belonging to the world academic community. The paper identifies main stages in the institutionalization of the history of science in St. Petersburg and demonstrates how these goals were achieved in changing socio-political and cultural contexts through different combinations of totalitarian and liberal policies. These combinations were determined by the state science policy, as well as by scientists’ strategies to use the history of science as a means to justify the utility of science for the state and society, and in this way to secure funding and material resources. The comparative historical analysis of dynamic changes in research agenda, projects, publications, forms and intensity of academic contacts and migrations provides a better understanding of the ways in which Russian scholars have been included in international academic networks, as well as their place in international research projects. Particular attention is given to the contribution made by Russian scholars to the social history of science at its formative stage. The paper examines the role of political, social and economic liberalization in the expansion of the research methods and approaches, the increase of publications and scholars’ mobility in the last two decades.